HEAT EXTRACTION MECHANISM USING SOLAR FOR AUTOMOTIVE INDUSTRY APPLICATION - Rijaluddin, Shahirah Atiqah (IRC, 2019)

(untitled)
The high ambient temperature in hot climate countries such as in Malaysia, Thailand and Indonesia may cause damage to the car interior and may give significant threat to children, disabled or elderly passengers. The work is initiated to reduce the temperature inside the parked vehicle that is directly exposed to the sunlight without starting the engine or turning the air conditioner to reduce the heat. Solar application is the best way to energise the system where it is placed on the rooftop of the car in order to absorb the sunlight’s heat for energy generation controlled by the charge controller and backed-up battery for energy storage. It is found that temperature has shown a decrement of few degrees to below 30 oC indicating the successful of the heat extraction mechanism once the system is implemented.